2015
DOI: 10.1080/01603477.2015.1065675
|View full text |Cite
|
Sign up to set email alerts
|

“Twin deficits” in Greece: in search of causality

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 35 publications
1
21
1
6
Order By: Relevance
“…Nesse sentido, os déficits governamentais causariam o déficit externo (Abell, 1990). Isso ocorreria por dois canais principais (Nikiforos et al, 2015). O primeiro canal sugere (baseando-se na teoria do Loanable Funds) que o aumento dos déficits públicos estimula a demanda, provocando uma situação em que o investimento doméstico supera a poupança doméstica.…”
Section: Padrões De Financiamento a Partir Da Abordagem Dos Balanços unclassified
“…Nesse sentido, os déficits governamentais causariam o déficit externo (Abell, 1990). Isso ocorreria por dois canais principais (Nikiforos et al, 2015). O primeiro canal sugere (baseando-se na teoria do Loanable Funds) que o aumento dos déficits públicos estimula a demanda, provocando uma situação em que o investimento doméstico supera a poupança doméstica.…”
Section: Padrões De Financiamento a Partir Da Abordagem Dos Balanços unclassified
“…8). In the case of the eurozone, many authors have argued that the high private and public deficits of the peripheral countries are simply the mirror image of the exogenous decrease of the current account balance due to the real exchange rate appreciation, the decrease in the transfers to these countries and the structural deficiencies of the eurozone (Arghyrou and Chortareas, 2008;Eichengreen, 2010;Chen et al, 2013;Flassbeck and Lapavitsas, 2013;Nikiforos et al, 2015;Kang and Shambaugh, 2016).…”
Section: Flow Of Funds (U)[memo: Net Lending]mentioning
confidence: 99%
“…These diagnoses reject the mainstream explanation of the crisis, which blames the allegedly profligate behaviour of southern countries. Taking the case of Greece as an example, Nikiforos et al (2015) have shown that the causality between the external to the fiscal deficit ran from the former to the latter, and not the other way around. According to these authors, 'the main source of the problem is to be found in the structural characteristics of the EMU ' (ibid.…”
Section: Introductionmentioning
confidence: 99%